Reaction Mechanism of Aluminum Toxicity on Leaf Growth of Shatian Pomelo Seedlings - Dan Tan; Jingfu Yan; Yali Yang; Shaoxia Yang; Lubin Zhang; Yingbin Xue; Ying Liu (Plants)
This study aimed to examine the effects of aluminum (Al) stress on the leaves of Shatian pomelo (Citrus maxima “Shatian Yu”) and its underlying response mechanisms. Leaf phenotype analysis, physiological response index determination, transcriptome analysis, and genome verification were employed to investigate the effects of Al toxicity in detail. Al toxicity stress inhibited leaf growth and development, reducing leaf area, girth, and both dry and fresh weights. Antioxidant enzyme activity and soluble protein content in leaves significantly increased with rising Al stress levels. Additionally, Al toxicity caused an accumulation of Al ions in leaves and a decline in boron, magnesium, calcium, manganese, and iron ion content. RNA sequencing identified 4868 differentially expressed genes (DEGs) under 0 mM (Control) and 4 mM (Al stress) conditions, with 1994 genes upregulated and 2874 downregulated, indicating a complex molecular regulatory response. These findings were further validated by real-time quantitative PCR (qPCR). The results provide critical insights into the molecular mechanisms of Shatian pomelo leaf response to Al toxicity and offer a theoretical basis and practical guidance for improving citrus productivity in acidic soils.